Inquiry and the National Science Education Standards : a guide for teaching and learning - Center for Science, Mathematics, and Engineering Education. Committee on Development of an Addendum to the National Science Education Standards on Scientific Inquiry (Washington, D.C. : National Academy Press, 2000)
Explains and illustrates how inquiry-based education can be used to teach science content, how to master science, and how to understand science concepts; with strategies for involving students, parental communication, and promoting National Science Education Standards.
Inquiry in science and in classrooms -- Inquiry in the National Science Education Standards -- Images of inquiry in K-12 classrooms -- Classroom assessment and inquiry -- Preparing teachers for inquiry-based teaching -- Making the case for inquiry -- Frequently asked questions about inquiry -- Supporting inquiry-based teaching and learning.
Includes bibliographical references (p. 153-158) and index.
Reference and Research Book News.
Science and Children (N.S.T.A.).
Professional
Keywords: Inquiry (Theory of knowledge); Science -- Study and teaching -- Standards -- United States; Science -- Study and teaching; Theory of knowledge